Analysis of attachment types among LGBTQ individuals - VASYLCHENKO, Olha; KONEV, Oleksandr (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
The analysis of attachment types among LGBTQ individuals is crucial because this group frequently faces additional challenges such as discrimination, internalized homophobia, and social isolation. These factors can significantly affect the formation of attachment types and overall mental health. Research in this area contributes to the development of effective psychotherapeutic approaches designed to support the LGBTQ community. The purpose of this study is to analyze attachment types among LGBTQ individuals to determine their impact on mental health and interpersonal relationships. This article is based on a systematic literature review. The study found that attachment types among LGBTQ individuals differ significantly from those among heterosexual individuals due to specific social and psychological factors. Peer relationships among sexual minorities influence their well-being and the formation of attachment types. Specifically, in homosexual men, attachment types significantly affect the quality of intimate relationships, underscoring the importance of secure attachment for a satisfying interpersonal life. Based on the analysis of scientific literature, it has been established that attachment types among LGBTQ individuals are shaped by minority stress, discrimination, social support, and interpersonal interactions. These factors can lead to the development of insecure attachment types, negatively impacting the mental health and quality of life of LGBTQ individuals. It is essential to understand that minority stress and discrimination create additional barriers to forming healthy interpersonal relationships and trust in others. The practical significance of this study lies in the necessity to develop support programs for LGBTQ individuals that focus on strengthening secure attachment. Such programs should include individual psychotherapeutic interventions aimed at overcoming the effects of discrimination and minority stress, along with group therapy sessions that provide support and opportunities for sharing experiences among LGBTQ individuals. Future research prospects include identifying effective methods to diminish the negative impact of discrimination and promote secure attachment among LGBTQ individuals. This encompasses both individual and group psychotherapeutic interventions that offer emotional support, foster self-regulation skills, and enhance self-esteem.